The experiences of female bisexual student-athletes in China: An interpretative phenomenological analysis - Xiang, Meng; Soh, Kim Geok; Xu, Yingying; Ahrari, Seyedali; Zakaria, Noor Syamilah (Frontiers in Psychology, 2023)
Introduction Many scholars have explored the participation of LGBTQ individuals in sports. However, these studies have either categorized homosexuality and bisexuality together or focused only on lesbian, gay, or transgender individuals. There is a lack of research in the literature on bisexual individuals’ sports participation and an even more significant lack of Asia perspectives. Therefore, this qualitative study is aimed to explore the experiences of female bisexual student-athletes in China. Methods Semi-structured interviews with four female bisexual student-athletes were conducted and analyzed using Interpretative Phenomenological Analysis (IPA). Results Three themes and eight sub-themes were identified. Theme 1. what bisexual identity means, and sub-themes: a struggling journey, emotional attraction, and gender role for female bisexual student-athletes; Theme 2. invalid identity, and sub-themes: lesbian mask, unrecognized identity; Theme 3. perceptions of sports context, and sub-themes: the influence of the sports context on sexual fluidity, relative inclusion, and perceived rejection. Conclusion This study provides new insights into understanding the experience of female bisexual student-athlete. In addition, the results highlight the importance of the need to study bisexuality as a distinct identity.